ILLUMINATING THE PATH TO EXCELLENCE: INSIGHTS FROM SAUDI ARABIAN NURSES ON ENHANCING PATIENT CARE QUALITY - Amani Ayed Ahmed Alanazi, Shaikhah Dhaifallah A Aldhafeeri, Latifah Dhaifallah Allaqti Aldhafeeri, Shifaa Dhaifallah Allaqti Aldhafeeri, Mastorah Abdul Mohsen Jailan Al-Azmi, Mutera Mohd Jadoa Alshamry (Chelonian Research Foundation, 2022)
The nursing profession in Saudi Arabia has undergone significant transformations in recent years, driven by the country's efforts to improve healthcare quality and meet the growing demands of its population. This qualitative study aimed to explore the perspectives and experiences of Saudi Arabian nurses regarding the factors that influence patient care quality and the strategies to enhance it. Semi-structured interviews were conducted with 20 nurses working in various healthcare settings in Riyadh, Saudi Arabia. Thematic analysis revealed five main themes: 1) professional development and education, 2) interprofessional collaboration and communication, 3) work environment and resources, 4) patient-centered care and cultural competence, and 5) leadership and organizational support. The findings highlight the importance of ongoing training and specialization, effective teamwork and information sharing, adequate staffing and equipment, respect for patients' values and preferences, and supportive management and policies in promoting high-quality nursing care. The study provides valuable insights for nurses, educators, managers, and policymakers to guide the development and implementation of strategies that foster nursing excellence and optimize patient outcomes in Saudi Arabia. Keywords: nursing, patient care quality, qualitative research, Saudi Arabia, thematic analysis